2013
DOI: 10.1519/jsc.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Fat and Dominant Somatotype on Explosive Strength and Aerobic Capacity Trainability in Prepubescent Children

Abstract: The purpose of this study was to analyze the influence of body fat and somatotype on explosive strength and aerobic capacity trainability in the prepubertal growth spurt, marked by rapid changes in body size, shape, and composition, all of which are sexually dimorphic. One hundred twenty-five healthy children (58 boys, 67 girls), aged 10-11 years (10.8 ± 0.4 years), who were self-assessed in Tanner stages 1-2, were randomly assigned into 2 experimental groups to train twice a week for 8 weeks: strength trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…In addition to changes in body size and composition, the prepubertal growth spurt is also marked by rapid changes in body shape (Malina and Bouchard, ). A recent study by Marta et al () showed that the morphological constitution affects training‐induced explosive strength and aerobic adaptations more strongly than fat mass in children aged 10‐ and 11‐ year‐old in Tanner stages I and II. In this study, the musculoskeletal magnitude on explosive strength and relative linearity on aerobic capacity have proven to be crucial factors related to training‐induced gains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to changes in body size and composition, the prepubertal growth spurt is also marked by rapid changes in body shape (Malina and Bouchard, ). A recent study by Marta et al () showed that the morphological constitution affects training‐induced explosive strength and aerobic adaptations more strongly than fat mass in children aged 10‐ and 11‐ year‐old in Tanner stages I and II. In this study, the musculoskeletal magnitude on explosive strength and relative linearity on aerobic capacity have proven to be crucial factors related to training‐induced gains.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the musculoskeletal magnitude on explosive strength and relative linearity on aerobic capacity have proven to be crucial factors related to training‐induced gains. In contrast, the relative adiposity has a negative effect on the training response (Marta et al, ). Furthermore, the literature reports that, during the prepubertal period, growth and dimensional increases are not accompanied by muscle development because the effects of circulating androgens, particularly testosterone, only manifest themselves at puberty (Ramsay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Representative data of VO 2max values in the young girls were scarce, presented within a wide range of age (i.e. [13][14][15][16][17][18][19], and vary among studies depending on sample size and measurement methods 3,8 . Our data are highly comparable with those reported in a study including 92 active and 75 non-active Spanish girls (41.85 mL/kg/min and 39.03 mL/kg/min in 12 to 18-years-old active and non-active girls, respectively) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to Robbins et al 15 , by the age of 13, only about 22% of girls meet World Health Organization recommendations of at least 60 min of physical activity every day 1,16,17 and almost 28% are already overweight or obese. These findings indicate that young girls would benefit from continuous involvement in exercise programs, such as those designed to increase physical activity 15,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in many studies on different branches, it is stated that the anthropometric features of the athletes have to be appropriate at the level of fulfilling the requirements of the sports branch in which they are engaged. It was demonstrated in many studies that the positive effects of anthropometric features of athletes on their development levels and athletic performances are very important for success (Marta et al, 2013;Vila et al 2009).…”
Section: Introductionmentioning
confidence: 99%